Variants of weightlifting method (progression) and its application in training practice especially considering the tempo of exercise performance - Kruszewski, M.; Olszewska, A.; Kuzmicki, S.; Kriszewski, A.; Landowski, K.; Tabecki, R.; Korczak, R.; Chec, R. (Journal of Combat Sports and Martial Arts, 2017)
The aim of the study was to present the modifications of weightlifting method, enabling the competitors to achieve maximal muscular stimulations, leading to the development of specyfic strength large muscle groups. The application goal was also determined, involving presentation of exercise sets used in strength sports and combat sports, developing specific strength in major muscle groups, particularly considering the tempo of exercising in each training sub-periods. The reference sources are reviewed as well as the earlier publications, describing the basic modalities of weightlifting method. The versions of this approach connected with methodical recommendations of Polish Weightlifting Method School, established by Augustyn Dziedzic are also presented. Each variant of weightlifting method is described in terms of its usefulness for developing maximal strength, anaerobic endurance, mastering motor habits (techniques), applying exercises which have a similar or a more complex structure than these previously applied and a fast tempo of exercising. Tempo variations are attributed to each sub-period of the training cycle, considering the frequency of application and exercise sets, aimed at the development of large muscle groups are presented. It is emphasized that weightlifting method should be regarded as a set of approaches, which, regularly applied, allow considerable increases of maximal muscular strength, anaerobic endurance and mastering motor habits. It has been confirmed that the application of different modalities of exercising tempo not only enriches their resources, but also can increase muscular strength and power, significantly contributing to the improvement of athletic performance in combat sports.